Attempted solution:

y=x/(xˆ2-4)

let y = inverse of y

x=y/(yˆ2-4)

xyˆ2-4x = y

xyˆ2-y-4x = 0

a = x, b = -1, c = -4x

y = (1 +/- sqrt(1-(4x)(-4x)))/(2x)

= (1+/- sqrt(1+16xˆ2))/2x,which is my solution

actual solution is:

y= (1-sqrt(16+xˆ2))/2x when x≠0

y= 0 when x = 0

I don't understand why the + sign has been discarded from the solution when x≠0 and I don't understand why y = 0 when x = 0. You could set y to 0 and solve for x in the original equation, but is that what is supposed to be done?

Thanks.